Localized and stress corrosion cracking of sensitized Al-Mg-Sc-Zr alloy manufactured by laser powder bed fusion. (1st July 2023) - Cabrera-Correa, Leticia; González-Rovira, Leandro; Ojeda-López, Adrián; de Dios López-Castro, Juan; Botana, F. Javier
Abstract: The effect of thermal ageing at 150 ºC on the corrosion behaviour of Scalmalloy® (Al-Mg-Sc-Zr) alloy additively manufactured by laser powder bed fusion (LPBF) is reported for the first time. Samples before and after the thermal treatment exhibit similar results on cyclic polarisation curves, electrochemical impedance measurements in 3.5 wt% NaCl, and tensile and hardness tests. However, electron microscopy characterisation reveals that the application of this temperature for sufficient time causes most of the grain limits to be decorated by Al3 Mg2 particles which in turn provokes the sensitization of the alloy to intergranular corrosion processes due to microgalvanic coupling. Highlights: Scalmalloy® manufactured under certified conditions is resistant to IGC and SCC. Ageing at 150⁰C produces a dense intergranular β-phase Al3 Mg2 network. Aged material becomes both IGC- and SCC-sensitised due to the β-phase network. The ageing does not significantly affect the mechanical properties of the material. The ageing does not significantly modify the pitting corrosion behaviour.